Waste Epoxy Moulding Compound as a Composite Gypsum Ceiling Board for a Sustainable Potential - 1wee1, 1wee1 (Progress in Engineering Application and Technology, 2023)
Epoxy moulding compounds are polymer-based encapsulation materials often used in electronic packaging. In recent years, the increasing electronic component output has resulted in a significant rise in the production of epoxy molding compounds as industrial waste from the molding process of electronic components packages. Therefore, this study investigated the potential of the waste epoxy molding compounds as a composite gypsum ceiling board to reduce gypsum use. It is in conjunction with the concept of a circular economy, which focuses on optimizing resources, reducing the consumption of raw materials, and recovering waste by recycling by giving it a second life as a new product. The composite materials were developed by a mixing method according to the proportion of the epoxy moulding compounds and the gypsum. Mixed proportions with five different percentages of epoxy moulding compounds, which are 0%, 5%, 10%, 15%, and 20%, were prepared and cast in an aluminum mold size of 10cm x 10cm x 1.27cm. The sample’s properties were analyzed for thermal conductivity, sound absorption, and water absorption. Hence, the optimum proportion of the composite gypsum ceiling board was identified, and the best results were 20% waste epoxy moulding compound and 80% gypsum for the better value of physio-mechanical properties of the composite materials. The result showed that the good thermal conductivity is 0.21W/m˚C, the maximum sound adsorption coefficient is 0.483 at 2000Hz, and the minimum water absorbency is 31.4%. Therefore, by exploring innovative recycling approaches might reduce the material waste and repurpose them as beneficial secondary products.